2005
DOI: 10.1007/s00191-004-0220-1
|View full text |Cite
|
Sign up to set email alerts
|

Technology-push, demand-pull and the shaping of technological paradigms - Patterns in the development of computing technology

Abstract: An assumption generally subscribed in evolutionary economics is that new technological paradigms arise from advances is science and developments in technological knowledge. Demand only influences the selection among competing paradigms, and the course the paradigm after its inception. In this paper we argue that this view needs to be adapted. We demonstrate that in the history of computing technology in the 20th century a distinction can be made between periods in which either demand or knowledge development w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…Paper [10] investigate the influence of technology and knowledge factors or market factors as enablers of innovation in computing technology. Technology factors refer to the speed and direction of technological knowledge.…”
Section: Information Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Paper [10] investigate the influence of technology and knowledge factors or market factors as enablers of innovation in computing technology. Technology factors refer to the speed and direction of technological knowledge.…”
Section: Information Technologymentioning
confidence: 99%
“…Market factors point to the rise or existence of a manifest or potential market for a product. Authors [10] concluded that development of computing technology has gone through three different phases: a demand enabled period between 1900 and 1960, and two knowledge enabled periods. The period between 1960 and 1990 was enabled by knowledge development in the field of microelectronics, while the period from 1990 to in fact the present was mainly enabled by knowledge developed for converging computing and telecommunications technology.…”
Section: Information Technologymentioning
confidence: 99%
“…Freeman [21] suggested that a new innovative pattern needs to be developed for large techno-economic system transitions. Van den Ende and Dolfsma [22] believe that the development of techno-paradigms is a result of the effects of push and pull, namely supply and demand. In competitive markets, Grübler et al [23] outlined how patterns, processes and timescales are characteristic of the new technological diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…A conclusion has been reached among industrial technologists according to which both factors (push and pull) are important (Dosi, 1982;Mowery and Rosenberg, 1979). Following this conclusion, the shift has been toward understanding the mix of economic, political, institutional, and technological factors that underlies innovations (Van den Ende and Dolfsma, 2005). In the financial innovation literature, the matter is still open.…”
Section: Emergencementioning
confidence: 99%